The growing peculiarities of pear tree planting material in conditions of Her-Her community of Vayots Dzor region - Gabrielyan, G. S.; Stepanyan, E. R.; Muradyan, A. K. (Հայաստանի ԳԱԱ «Գիտություն» հրատ.)
The current work pursues production goals, particularly from the prospect of expansion of pear tree nurseries. In our republic the great part of pear tree nurseries dries out due to the bacterial leaf blight, improper selection of rootstock and scion (grafter) varieties, as well as to the random selection of rootstocks. Analyses on the planting stock quality have been conducted during the work implementation in the nursery farm of Herher community considering the inosculation results of various rootstocks. Application of different rootstocks in the nursery farms promotes the establishment of saplings with high survival rate and productivity. It is impossible to develop the branch of horticulture in the Republic of Armenia without the operation of nuresery farm system and sustainable production of healthy, purebred, reliable and high quality planting material. It is relevant to use the seed plants of Willow-leaf pear tree and quince tree rootstock for the pear tree varieties investigated by our research group. Propagation via shrubs has been singled out as an efficient method for clonal rootstock propagation. Աշխատանքն ունի արտադրական նշանակություն հատկապես տանձենու տնկարկների ընդլայնման գործում: Հանրապետությունում տանձենու տնկարկների մեծ մասը չորանում է բակտերիալ այրվածքի պատճառով, սխալ ընտրված պատվաստակալ և պատվաստացու սորտերի, պատահական պատվաստակալների ընտրության արդյունքում: Հերհեր համայնքի տնկարանային տնտեսությունում աշխատանքի կատարման ժամանակ, հաշվի առնելով տարբեր պատվաստակալների համաճի արդյունքները, կատարվել են վերլուծություններ տնկանյութի որակի վերաբերյալ: Տնկարանային տնտեսությունում տարբեր պատվաստակալների կիրառումը նպաստում է բարձր կպչողականությամբ և արտադրողականությամբ տնկարկների հիմնադրմանը: Հայաստանի Հանրապետությունում առանց տնկարանային տնտեսության համակարգի գործունեության, առանց առողջ, մաքրասորտ, հուսալի ու հայտնի որակի տնկանյութի կայուն արտադրության հնարավոր չէ զարգացնել պտղաբուծություն: Ուսումնասիրությունների արդյունքում պարզվել է, որ լավագույն պատվաստակալներ են համարվում ուռիատերև տանձենու սերմնաբույսերը և սերկևիլենու արմատակալները: Работа имеет производственное значение, особенно в деле расширения площадей насаждений. Большинство насаждений груши в республике высыхают от бактериального ожога, в результате неправильного избрания подвоя и привоя, случайного подбора подвоев.В питомнике, находящимся в общине Гергер, во время нашего исследования учитывая результаты срастания различных подвоев, были проведены анализы о качестве саженцев. В питомнике использование различных подвоев дает возможность для закладки высокой приживаемости и продуктивности насаждений. В РА невозможно развивать устойчивое плодоводство без скоординированной деятельности питомника и производство здоровых, чистосортных, надежных, известных, качественных саженцев. Исследования показали, что лучшими подвоями являются сеянцы иволистой груши и отводы айвы.
Keywords: Agriculture